Correlation Between Body Mass Index and Biological Age in Young Adults (Nusantara Science and Technology Proceedings, 2022)
Background: Biological age is influenced by several factors including nutritional status. Body mass index (BMI) is an anthropometric measurement that can be used to assess a person's nutritional status. Objective: The purpose of this study was to determine the correlation between MT and biological age. Methods: Cross-sectional study on students of the Faculty of Medicine and Faculty of Nursing, the University of Riau in March – October 2022, n= 90 people, with consecutive sampling. Results: BMI has a significant, positive, and very strong correlation with biological age (p < 0.001, r = 0.965). Conclusion: The higher the BMI, the older the biological age, so that by reducing BMI is expected to improve biological age.